MITIGASI PERUBAHAN IKLIM MELALUI PENANAMAN MANGROVE DI DESA LHOK BUBON KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Mira Mauliza Rahmi; Nabil Zurba; Dini Islama; Friyuanita Lubis; Mai Suriani; Neneng Marlian; Ikhsanul Khairi; M. Arif Nasution; Zulfadhli Zulfadhli (Universitas Teuku Umar, 2022)
Mitigation of climate change is a business activity to reduce the risk of increasing greenhouse gas emissions in the atmosphere, gases can occur naturally in the environment and can also arise due to human activities. Mangroves are carbon-rich ecosystems and have an important role in climate regulation, namely by their ability to store large amounts of carbon as an effort to offset anthropogenic CO2 emissions. Mangrove ecosystems are able to store high carbon which is useful in reducing greenhouse gas emissions, mangrove ecosystems are also able to store carbon three to four times greater than ordinary tropical forests. The activity was carried out in Lhok Bubon Village, Samatiga District, West Aceh District. This activity was attended by the academic community of FPIK UTU with 50 participants. The method of implementing community service activities used was counseling and demonstration methods with students through planting 100 mangrove stems, namely Rhizopora sp. Protecting the mangrove ecosystem is our common awareness, especially students as the next generation of the nation, one of which is by not cutting down mangrove trees to be used as firewood or charcoal, opening up ponds and destroying the original habitat of mangrove ecosystems that can disrupt coastal aquatic biota. Students are given education (counseling) about the importance of conserving mangrove ecosystems from the threat of climate change mitigation. Students are very enthusiastic and active, it can be seen from the seriousness in participating in mangrove planting activities through discussions, questions and answers, and hands-on practice. Sustainability of a program like this is needed and efforts are made to become a routine program of gampong activities, NGO activities and also academic activities, because with sustainability it will be faster to see the results that have been expected together.